Software for teaching aid: electrical power engineering concept / Hairulazwan Hashim - Hashim, Hairulazwan (2003)
The main objective of this project is to design a software especially for Electrical Engineering students and to assist them in learning the electrical power engineering subject. The project centered on the Computer Aided Education software and it was developed by using Matlab and Simulink programming languages. The text and graphics are included to provide simulation of the electrical power engineering concepts and also to be an interactive teaching notes, diagrams, and interactive graphics. The learning process using this software becomes more stimulating, easier to understand. The potential of the software includes; expanding the contents, assisting and improve the teaching and learning process. All the features in this software are user friendly and interactive.